Shades of Housing: Real Estate Urbanism and State Planning in Egypt - Nadeem, Zeinab (AUC Knowledge Fountain, 2023)
The housing crisis is a global dilemma, especially in the context of urban cities in developing countries. Housing affordability has become more challenging in the recent global and national turbulent economic conditions of rising inflation rates and construction costs, where Egypt is witnessing a surplus of vacant housing units that are either unsold or unoccupied with citizens involuntarily relocating to remote new cities. The government has also significantly engaged in real estate market speculation by offering public land for profits to private investors in the market since the 1990s. The shades of housing found in Egypt are the works of the formal public sector, the formal private sector, and the informal private sector, where the abundance of vacant housing is the byproduct of state and real estate housing provisions. This research investigates the approach of real estate developers in housing provisions for the middle classes of Egypt. To answer this question from the developers’ perception, a set of 23 interviews were conducted with decision-makers in real estate developers operating in Egypt, real estate consultants, and urban scholars to analyze the urban phenomena of gated communities within the context of governing state policies. Through an inductive analysis approach, the main findings and results explore four major aspects from the perspective of those developers on their own ‘informal’ formal practices of building exclusive and elitist communities that widen gaps between the middle classes of Egypt. The four main components are their perception of their own different typologies in operation and practice in the market, of the consumers, of their different power classes and hierarchy in the context of market competition and the different classes of society, and of the role of government. Some of the major findings include acknowledging the role of affluent citizens as players in the aggravation of social segregation by gated communities. The technological advancements and urban transformations within the Egyptian society has led to the creation of new middle classes that aspire to own property in gated communities, categorized by developers as A, B, C, D classes. However, the unstable economic situation has increased the affordability gap for them, where a big portion of them can no longer afford property ownership and struggle to find affordable investment opportunities like the practices of more affluent classes to retain the value of their savings in such a speculative real estate market. Egypt’s housing problems for the middle classes necessitate interventions from the state to introduce a multidisciplinary, integrated system of policies that encourages the spread of non-gated residential developments which respond to the needs of communities, enhance social cohesion across classes, and offer alternative investment opportunities.